USING FLASH CARD ON YOUNG LEARNERS’ ENGLISH VOCABULARIES MASTERY AT GB (GURU BAHASA ) STUDENTS IN PARE KEDIRI - Kulsum, Ummu; Ahmadi; Hayyul Mubarok (Pendidikan Agama Islam, 2024)
Nowdays, English vocabularies is taught in early young learners Elementary school around 1-4 grade. Hopely, the early vocabulary learning can stimulate the learners in knowing and to memorize the simple English vocabularies naturally. Then, they have a strong memorization and many vocabularies. In this case, the researcher hypothesizes that the English by using flash card can be an alternative for young learners to stimulate them in finding and knowing new English vocabularies as fun as possible. So they are not aware that they are studying and memorizing many English vocabularies whiles they like playing around, but they got many English vocabularies in their early life. The study mainly aimed at measuring the effectiveness of using English Flash card on young learners’ English vocabularies mastery at GB students of elementary level. English by using flash card is a card that consist of many vocabularies with the picture and has colorfully pictures. where students can acquire the vocabularies and practice their English language skills. There are two problem statements in this study. The first one is whether the English by using flash card have the effectiveness on the young learners’ English vocabularies mastery or not. The second is How significance is the effectiveness of English by using flash card to the young learners’ English vocabularies mastery. The subject of this study is B class GB students which consists of 43 students. Research instrument which are used are tests (pre-test and post-test) and documentation as the major instruments, also observation and interview as the secondary instruments. The study took place for two weeks, from March 23nd until April 6th. The obtained data of tests was analyzed by using dependent t-test (one group pre-test post-test design) formula. The result showed that there is an effectiveness of using English using flash card on young learners’ English vocabularies mastery; and the effectiveness of using English flash card is statistically significant on young learners’ English vocabularies mastery either in 5% level significance or in 1% level significance. It was proven by the result of the obtain data, t0 is greater than ttable (6,48>2,02 or 2,69). It can be drown a conclusion that English by using flash card setting in the classroom have an efectiveness on young learners ability to master vocabulary. It is proven by the average of post-test scores is higher than the average of pre-test scores. It means